CHINESE AND AFRICAN MIGRANT ENTREPRENEURS' ARTICULATION SHAPED BY AFRICAN AGENCY (The Strategic Review for Southern Africa, 2020)
Much has been written on the relationship of China and Africa in the past decade. However, the subject of Chinese migrant entrepreneurs in Africa and their articulation with African counterparts was little explored up to the early 2010s. Apparently, this research gap has been closed, as shown by four publications in recent years: three edited volumes and one monograph, focusing on this subject. In view of early prejudices on the passive or even disapproving reception of Chinese migrants by Africans, the state of the art underlines the importance and scope of African agency vis à vis Chinese migrant entrepreneurs in Africa. This has been underlined unison in the four books under review.